Corrupção e violação dos direitos humanos: um fenômeno ― “glocal” a partir da Nona Sinfonia de Beethoven - Castilho, Carla Dalenogare (2019)
This paper presents a international corruption study in order to connect with Mireille Delmas-Marty's work “Three Challenges for a World Law”, recognizing that social rights are part of human rights (human rights), considering the new powers that rules the world (Transnational X Executive Power). Through the metaphor of Ludwig van Beethoven's Ninth Symphony, it aims to address the human rights concussion that international corruption causes by undermining social rights. In order to reflect about possible obstacle that corruption represents to Global Law, being a relevant factor for disadvantage of social rights and individual liberty that affect the human rights of the network society, the following question is asked: “Which are the risks that corruption poses to Global Law as a civilizational platform? ”. For this, the phenomenological-hermeneutic “method” was used, not here as a method, but as an unveiling of being-in-the-world in its possibilities, opting for the Heideggerian understanding of method, in a way of unveiling in an “eternal”/“continuous” redesign of possibilities of being-in-the-world, which allows a (re) thinking about corruption by the democratic-constitutional and universal order that human rights inhabit.Thus, the first chapter worked with the colonizing philosophy embodied in the history of international law and its social and philosophical implications in defining an idea of global justice. Everything to make it possible to study the concept and challenges of defending the (possible?) construction of a human community of values, being necessary to understand the concept of humanity that implies understanding the human and non-human binomial and common humanity patrimony. Considering that this paper had its formal essence bibliographic, the proceeding used was historical, considering the fact that the history of the theme is sought, situating the subject in space and time. Regarding the research technique, it is used indirect documentation, making use of doctrinal references published in scientific documents, such as doctrinal works, articles, journals and magazines, among others. In the second chapter, it’s intended a reflection about the role, the place and the space that Law occupies in front of the democratic evil of corruption, as well as the need to elaborate new legal categories. Thus, it is necessary to understand the legal category in which society finds itself (as a victim?) in order to (if possible) categorize corruption as a crime against humanity, but, before that, it is intended to contextualize crime against humanity.